Creativity profile of biology teacher candidates: An exploratory study - Setiono; Windyariani, Sitiana; Agustiani, Nur (Biosfer: Jurnal Pendidikan Biologi, 2024)
Abstract: Creativity is one of the important skills that teachers must have today. Creativity can be defined as the human ability to generate new and valuable ideas. In addition, creativity is considered as a basic competency that needs to be possessed by students in higher education. The purpose of this study was to determine the creativity of prospective biology teachers and its relationship with students' knowledge mastery. For this purpose, a descriptive and correlational study was conducted on 13 biology pre-service students. The instrument used in this study was the Torrance creativity test based on 4 creativity indicators: fluency, flexibility, originality and elaboration. Descriptive and correlational analyses were conducted to identify students' creativity profiles and the relationship between students' creativity and their knowledge mastery. The results showed that there were three types of creativity owned by prospective biology teacher students, namely students with low (38.46%), medium (38.46%) and high (23, 07%) levels of creativity. The correlation test results show that concept mastery correlates with student creativity (r=0.3). The conclusion of this study is that prospective biology teacher students have different creativity, and there is a correlation between students' concept mastery and their creativity level so that there needs to be an effort from lecturers by designing learning strategies that can increase student creativity and concept mastery.